Feminist links between socorristas and health professionals to expand abortion rights in San Juan. The prelude to the implementation of the IVE Law (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
Previous to the legalization of abortion in Argentina at the end of 2020, some provinces of the country guaranteed the practice in the health system under certain circumstances. In the rest of the provinces, including San Juan, those in need were prevented from accessing abortions in the health system. In addition to the legal circumstances, in any context there were multiple difficulties in accessing safe abortion practices. Such conditions prompted feminisms to organize accompaniment practices, providing information and care to those who needed abortions. With the advent of the pandemic in the early 2020s, difficulties in accessing abortion increased. This article investigates the strategies of socorristas and health workers during that period to generate an opening in the abortion services of the health system of San Juan and thus federalize the exercise of existing rights. A qualitative methodology is adopted from an interpretative approach that combines key informant interviews with ethnographic work with feminist activists and health professionals.
Keywords: Abortion politics; Socorristas en Red; health professionals; pandemic; San Juan